Light-induced optical absorption in the garnet Ca₃Mn₂Ge₃O₁₂ - Bedarev, V.A.; Gnatchenko, S.L.; Rupp, R.A.; Sugg, B. (Физика низких температур, 1998)
Light-induced change in the optical absorption of the garnet Ca₃Mn₂Ge₃O₁₂ has been found. The magnitude of the light-induced optical absorption does not depend on the polarization state of the exciting illumination. The effect persists for a long time at low temperatures and can be attributed to light-induced generation or redistribution of Mn ⁴⁺ ions in the crystal.